T2-weighted magnetic resonance imaging to assess myocardial oedema in ischaemic heart disease. Issue 16 (15th May 2009) - Edwards, N C; Routledge, H; Steeds, R P
Abstract : Cardiovascular magnetic resonance imaging (CMR) is an established clinical tool for the identification of irreversible myocardial injury. More recently, experience with stress-perfusion CMR has increased sufficiently so that this now provides an accurate and reliable aid to clinical decision-making in patients with ischaemic heart disease. T2-weighted or "black blood" imaging is a technique used less frequently to examine the myocardium but one that is growing in stature. This article explains the rationale behind the technique and reviews recent data illustrating clinical and research scenarios in which the addition of T2-weighted sequences to standard cardiac scanning protocols might be warranted.